Environmental liabilities and diversity in practice under international financial reporting standards. Issue 2 (20th February 2017) - Schneider, Thomas; Michelon, Giovanna; Maier, Michael
Abstract : Purpose: The purpose of this paper is to encourage accounting regulators to address diversity in practice in the reporting of environmental liabilities. When Canada changed to International Financial Reporting Standards (IFRS) in 2011, Canadian regulators asked the IFRS Interpretations Committee to interpret whether the discount rate to value environmental liabilities should be a risk-free discount rate. Old Canadian GAAP, and current US GAAP, allow for a higher discount rate, resulting in commensurately lower liabilities. International regulators refused to address this issue expecting no diversity in practice in Canada. Design/methodology/approach: The focus is on a sample of Canadian oil and gas and mining firms. These domestic industries play a major role internationally and have significant environmental liabilities. The method is empirical archival, tracking firm characteristics and discount rate choice on transition to IFRS. Findings: There is significant diversity in practice. About one-third of the sample firms choose a higher discount rate, avoiding a major increase in environmental liabilities on transition to IFRS. The evidence suggests that these firms have relatively larger environmental liabilities and that the discount rate decision is a strategic choice. Research limitations/implications: The sample is based on one country and may only be reflecting local anomalies that have no broader implications. Practical implications: Diversity in practice in accounting for environmental liabilities is not acceptable. Accounting regulators should act to create consistent and comparable reporting practice. Social implications: Firms and managers facing larger environmental liabilities can choose to minimize environmental liabilities under IFRS, while it is the general public and society at large that bear the ultimate risk. Originality/value: The paper pushes forward the debate on whether recognized environmental liabilities should reflect the interests of equity investors, or if other investors and stakeholders should be taken into account.